The Ethnomathematics of the Orem Sasadu Sahu Tribe: Reconstructing Mathematical Concepts from Cultural Activities - Suharna, Hery; Hi Abdullah, In; Supratman, Supratman; Rasid Saputra, Lamanisa (IJORER : International Journal of Recent Educational Research, 2026)
Objective: This research examines the process of constructing mathematical concepts, which is very interesting and important. The principles of mathematical constructivism are closely linked to information processing theory in constructing concepts and reconstructing new information. This research aims to determine how mathematical reconstruction occurs in a theoretical and practical study of the fundamental activities of the Orem Sasadu Sahu Tribe on Halmahera Island. Method: This research is a qualitative research with an ethnographic approach. The data analysis used is the methodical elements, namely description, interpretation, historical continuity, and heuristic. Furthermore, data acquisition is by field study methods, exploration, observation, interviews and documentation. In this study, the focus is on fundamental activities (1) determining time, (2) calculation, (3) counting, and (4) measuring. The data analysis technique used is a qualitative data analysis technique. Results: This research obtained the results that (1) The construction of mathematical thinking is the activity of measuring to determine the amount of wood needed which is connected to the concept of geometry. (2) The construction of mathematical thinking is the activity of calculating and measuring to determine the amount of wood needed which is connected to the concept of natural number operations patterned like rows and series in mathematics; (3) The construction of mathematical thinking is the activity of determining how long the material must be cut, how long the renovation must take and the length of time. Novelty: The study of mathematical thinking constructs in Orem Sasadu activities is unique and interesting to examine. These constructs yielded three findings: measuring, calculating, and determining time.